Transformasi Spreadsheet menjadi Diagram Business Process Model and Notation melalui Pendekatan Rule-Based - Santoso, Teguh Budi; Yaqin, Muhammad Ainul (TIN: Terapan Informatika Nusantara, 2025)
Business process modeling plays an essential role in helping organizations improve operational efficiency and maintain process consistency. However, many organizations still rely on spreadsheets as a medium for documenting processes, which requires manual interpretation before being converted into Business Process Model and Notation (BPMN) diagrams. This study develops an automated rule-based method to transform spreadsheet content directly into BPMN diagrams. Each row in the spreadsheet is analyzed and mapped into process elements such as activities, events, decision points, and process flows. The method includes data normalization, structural mapping, BPMN XML construction, and structural validation to ensure compliance with BPMN standards. The experiments were conducted using three business process datasets from cooperative finance, poultry farming, and academic writing services. Each process contained between 21 and 29 activities, providing sufficient structural variation to assess the reliability of the method. The similarity between the automatically generated diagrams and manually created diagrams was measured using a label-based similarity approach, yielding values ranging from 0.85 to 1.00. These results indicate that the automated rule-based method can produce BPMN diagrams that closely reflect the accuracy of human-created models. This study offers practical benefits such as faster process modeling, improved documentation consistency, and support for business process digitalization in organizations that rely on spreadsheets as their primary source of process information.